Chemical compounds in essential oils of Espeletia spp. endemic from Colombia and preliminary evaluation of their antimicrobial activity - Gutiérrez Hernández, Doris (2024)
This study identifies the chemical compounds present in the essential oils of five species of frailejones and evaluates their biological activity against various microorganisms. The essential oils from the fresh leaves of Espeletia argentea, Espeletia barclayana, Espeletia killipii, Espeletia summapacis, and Espeletiopsis corymbosa were extracted through hydrodistillation. The chemical composition of the essential oils was determined using gas chromatography-mass spectrometry (GC-MS). The essential oils of some species were tested against fungi (Fusarium sp., Chaetomium sp., Botrytis sp., Penicillium sp., Alternaria sp.) and the bacteria Staphylococcus aureus ATCC 25923, as well as the yeast Candida sp., using the agar diffusion method. The major compounds identified in the essential oils were α-pinene, β-pinene, sabinene, p-cymene, limonene, and α- and β-phellandrene. Additionally, the essential oils of four Espeletia species exhibited activity against Fusarium sp. and Chaetomium sp. when compared to a commercial control. Furthermore, the oils of E. argentea and E. corymbosa were subsequently tested against strains of Botrytis sp., Penicillium sp., and Alternaria sp. It was found that the essential oil of E. argentea exhibited inhibition rates ranging from 30% to 80% against the tested strains.